LIQUID METAL FLOW CONTROL BY DC ELECTROMAGNETIC PUMPS - Borges, E. M.; Braz Filho, F. A.; Guimarães, L. N. F. (Revista de Engenharia Térmica, 2010)
The cooling system of high-density thermal power requires fluids of high thermal conductivity, such as liquid metals. Electromagnetic pumps can be used to liquid metal fluid flow control in cooling circuits. The operation of electromagnetic pumps used to flow control is based on Lorentz force. This force can be achieved by magnetic field and electric current interaction, controlled by external independent power supplies. This work presents the electromagnetic pump operational principles, the IEAv development scheme and the BEMC-1 simulation code. The theoretical results of BEMC-1 simulation are compared to electromagnetic pump operation experimental data, validating the BEMC-1 code. This code is used to evaluate the DC electromagnetic pump performance applied to Mercury flow control and others liquid metal such as Sodium, Lead and Bismuth, used in nuclear fast reactors.